1999
DOI: 10.1007/s11745-999-0476-3
|View full text |Cite
|
Sign up to set email alerts
|

Separation and determination of glycolipids from edible plant sources by high‐performance liquid chromatography and evaporative light‐scattering detection

Abstract: Glycolipids from edible plant sources were accurately quantified by silica-based, normal-phase high-performance liquid chromatography using an evaporative light-scattering detector. Five major glycolipid classes (acylated steryl glucoside, steryl glucoside, ceramide monohexoside, monogalactosyldiacylglycerol, and digalactosyldiacylglycerol) were separated and determined with a binary gradient system consisting of chloroform and methanol/water (95:5, vol/vol) without any interference from other lipid classes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
162
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(176 citation statements)
references
References 39 publications
(51 reference statements)
5
162
4
Order By: Relevance
“…Moreover, the results of the present study show that the respective contents of these dietary sphingolipids per day were approximately 292 mg and 128 mg with the HC meals, and 81 mg and 45 mg with the LC meals ( Table 2). In respect of cerebroside, Sugawara and Miyazawa have previously estimated a daily intake of 50 mg, 16) the content of cerebroside in the present study ranging from 26 to 77 mg. Plant cerebroside is currently on the market as a sphingolipid supplement for skin care. It has been reported that an effect on epidermal moisture retention can be expected when dosing 1 mg of a cerebroside concentrate per day.…”
mentioning
confidence: 44%
See 4 more Smart Citations
“…Moreover, the results of the present study show that the respective contents of these dietary sphingolipids per day were approximately 292 mg and 128 mg with the HC meals, and 81 mg and 45 mg with the LC meals ( Table 2). In respect of cerebroside, Sugawara and Miyazawa have previously estimated a daily intake of 50 mg, 16) the content of cerebroside in the present study ranging from 26 to 77 mg. Plant cerebroside is currently on the market as a sphingolipid supplement for skin care. It has been reported that an effect on epidermal moisture retention can be expected when dosing 1 mg of a cerebroside concentrate per day.…”
mentioning
confidence: 44%
“…13,14) It is considered that the routinely ingested sphingolipids are mainly sphingomyelin from animal foodstuffs and mainly cerebroside from plant foodstuffs. 15,16) In reports concerning the intake of sphingolipids, Vesper et al have summarized the amounts of sphingolipids in foods from estimated data in the available literature; 15) however, their class and how much sphingolipid is ingested daily have not been clarified. In addition, Sugawara and Miyazawa have reported the daily intake estimated from the contents of cerebroside in various plant foodstuffs.…”
mentioning
confidence: 99%
See 3 more Smart Citations